Response of Pinus tabuliformis saplings to continuous autumn fertilization treatments in the mountains of Eastern Liaoning Province, China - Zhang, Yiming; Han, Jincheng; Wang, Lijiao; Jing, Xin; Wang, Yutao; Liu, Ping (PeerJ, 2022)
Autumn fertilization is an important cultivation and management measure used to provide nutrients at the hardening stage during the end of the growing season—bolstering nutrient reserves and promoting additional growth in the following spring. Previous studies mainly focused on short-term or one-time fertilization treatment of container seedlings, and few studies have observed the effects of autumn fertilization of large-area forests over multiple continuous years. The growth dynamics and nutrient changes during autumn in 324 Pinus tabuliformis saplings in the temperate zone of China (in the eastern Liaoning mountains) were studied under field conditions with different fertilizer treatments for three consecutive years. The second year of autumn fertilization promoted the growth of tree height and annual leaf length more significantly than that in the first year, the change in diameter at breast height (DBH) was significant. Tree height (TH) in spring increased at a faster rate than in autumn, while DBH stably increased throughout the year. The increase in TH, DBH, and annual leaf length (ALL) under all fertilization treatments was higher than that of the control group, and the decrease in annual branch length (ABL) was higher than that of the control group. High N significantly increased the concentration of new coniferous N (NLN), soil total N (STN), and soil alkali-hydrolyzable N (SAHN) in P. tabuliformis saplings. High P significantly increased the concentration of P in annual needles and soil total P (STP), and decreased the concentration of N in new needles. In addition, there is a certain correlation between the N and P concentration in the needles and soil, representing the competition and interactions between plant nutrient demand and soil nutrient supply. The most favorable fertilizer treatment consisted of high N and low P (urea 204 g, calcium superphosphate 104 g), which provide support for the formulation of a reasonable fertilization technology for P. tabuliformis in the mountains of Eastern Liaoning Province, China.
Keywords: Autumn fertilization; Growth dynamics; Nutrient change; Pinus tabuliformis; Saplings